107 Remote ischaemic preconditioning and human atrial trabeculae in the diabetic heart. (16th May 2012) - Sirohi, R; Candilio, L; Babu, G; Roberts, N; Lawrence, D; Sheik, A; Kolvekar, S; Yap, J; Hausenloy, D J; Yellon, D M
Abstract : Introduction: Remote ischaemic preconditioning (RIPC) using brief cycles of upper or lower limb ischaemia and reperfusion has been reported to protect the heart against ischaemia-reperfusion injury (IRI). Previous studies suggest that the diabetic heart is more resistant to the cardioprotective effects of myocardial ischaemic preconditioning. Whether the diabetic heart is amenable to RIPC is unknown and is investigated in this study. Methods: Non-diabetic and diabetic patients undergoing elective coronary artery bypass graft (CABG) surgery were randomised to receive three different treatment protocols after the induction of anaesthesia: (1) Control—no RIPC; (2) RIPC1 comprising 3-five min cycles of upper arm cuff inflation/deflation; or (3) RIPC2 comprising 2-five min cycles of simultaneous upper and lower limb cuff inflations/deflations (total 4). A section of the right atrial appendage was harvested, from which atrial trabeculae were isolated and subjected to 90 min simulated ischaemia and 120 min simulated reperfusion, at the end of which the recovery of baseline contractile function was determined. Results: Atrial trabeculae harvested from diabetic (N=13 patients) and non-diabetic control patients (N=20 patients) were demonstrated to recover 24.5%±2.4% and 29.3%±1.3% of baseline contractile function, respectively. Prior treatment of patients with RIPC1 increased the recovery of function in both non-diabetic (50.4%±1.9%; p<0.05) and diabetic (41.6%±1.9%; p<0.05) patients. Interestingly, the stronger RIPC2 stimulus resulted in a greater recovery of function in both non-diabetic (59.3%±1.9%; p<0.05) and diabetic (50.7%±2.1%; p<0.05) patients. As a positive control direct hypoxic preconditioning (HPC) of atrial trabeculae also improved the recovery of function (56.4%±1.8% with HPC vs 27.5%±1.7% in control; N=10 patients; p<0.05). The administration of the MEK-Erk1/2 inhibitors U0126 and PD98059 at the onset of reperfusion abrogated the protective effect in both non-diabetic (30.9%±0.8% U0126 and 31.3%±0.8% PD98059; p>0.05) and diabetic (28.6%±0.9% U0126 and 30.0%±1.2% PD98059; p>0.05) atrial trabeculae. Conclusion: We demonstrate for the first time that in vivo RIPC can protect ex vivo atrial trabeculae against simulated IRI. Both non-diabetic and diabetic atrial trabeculae were amenable to RIPC protection. Increasing the intensity of the RIPC stimulus resulted in greater functional recovery. The pro-survival kinase MEK-Erk1/2 appears to contribute to RIPC protection in human atria trabeculae.